Analisis Sifat Mekanis Camshaft Sepeda Motor Kondisi Standar dan Rekondisi Dengan Proses Quenching - Alfian Sidik; Aa Santosa; Deri Teguh Santoso (Jurnal Ilmiah Wahana Pendidikan, 2023)
In this study, the camshaft repair process was carried out on motorbikes with the aim of restoring the profile of the camshaft that had been worn out, so that the valve opening and closing time was again in accordance with the cycle of a four stroke engine. From the results of the performance test (dyno test) of the standard camshaft, the maximum power produced is a standard camshaft with a power of 10.05 HP at 8654 rpm and 10.70 N.m of torque at 5772 rpm. Reconditioned camshaft with 10.07 HP of power and 15.46 N.m of torque at 3982 rpm. The mechanical properties produced by the Camshaft are the results of standard Camshaft testing 209 HBN, Reconditioned Camshaft 198.5 HBN, Reconditioned Camshaft (HT) 212.66 HBN. Then for the metallographic test results of standard camshafts and reconditioned camshafts, they both show the structure of graphite nodules surrounded by ferrite in a pearlite matrix